Tinjauan ontologis terhadap objek pengetahuan dalam filsafat ilmu - Sari, Rika Yohana; Jasrial, Jasrial; Sulastri, Sulastri (Universitas Cokroaminoto Yogyakarta, 2024)
Philosophy of science encompasses reflective thinking about the foundations of science and its relationship with human life. The purpose of this writing is to elaborate ontological views on the objects of knowledge in the philosophy of science. The method used in the research is literature study, where the author conducts a review of various books and related scholarly works. The analysis results conclude that philosophical studies involve exploring the integration of various types of knowledge through an examination of ontological aspects. This explains that the scope of objects of knowledge is not only limited to the concrete, but also includes metaphysical or abstract aspects. Both, concrete and abstract, are part of interrelated fields of study. Science plays a crucial role in human social life, serving as an indicator of a nation's progress. Therefore, it is important for philosophers to formulate rational and structured frameworks related to scholarly research. This impetus inspires the emergence of the philosophy of science, a branch of knowledge specifically examining the essence of knowledge itself. As a result, it generates various fields of knowledge, including social sciences and all their branches. In its context, ontology emphasizes the essence of knowledge, with the aim of strengthening the truth of that knowledge.